Soil erosion susceptibility mapping using a GIS-based multi-criteria decision approach: Case of district Chitral, Pakistan - Aslam, B. (Ain Shams University, 2021)
Soil erosion has serious threats to agricultural production, hydraulic structures, and the world's ecosystem. The objective of this study is the delineation of soil erosion susceptibility zones in the Chitral district using spatial analyst tool in conjunction with Analytical Hierarchy Process (AHP). This district is highly vulnerable to soil erosion due to the mountainous topography. For the sustainability of agricultural land use as well as regional and local development, it is necessary to find out soil erosion probability zones and soil loss at the watershed scale. Eleven different factors; lithology, slope, elevation, plain curvature, lineaments, land cover, aspect, rainfall, drainage density, NDVI (Normalized Difference Vegetation Index) and NDWI (Normalized Difference Water Index) are considered in this study. Weights have been assigned to each factor, and maps have been generated through GIS (Geographic Information System) tools. The final map from the combination of all maps shows intensities of soil erosion in five different classes including very high, high, medium, low and very low. Very high and high erosion is observed in 13 and 18 of the total study area respectively, which shows that area is under serious danger of soil erosion. Elevation, slope, curvature, NDWI, and rainfall are found to be the dominant factors influencing soil erosion process. This study highlighted areas at risk of severe erosion which will be helpful for researchers and planners to plan for control of soil erosion. Â© 2020 THE AUTHORS